Community Assessment of Salafi Studies in the City of Padang - Mutathahirin, Mutathahirin; Hudamahya, Aulia; Hamdi, Hafizul (International Journal of Multidisciplinary Research of Higher Education, 2020)
This research aims to analyze the public's assessment of Salafi studies. This research was conducted using quantitative methods with a survey approach. The data source was taken using a questionnaire from one hundred people in the community who were selected using techniques of simple random sampling. The questionnaire data was analyzed descriptively using IBM SPSS Statistics 26 software. Overall the research results showed five public assessments of Salafi studies in Padang City. The five assessments are i) the development of Salafi studies in Padang City, ii) the preaching of monotheism in Salafi studies, iii) acceptance of Salafi studies in Padang City, iv) Salafi is not a sect or group, v) is based on pure Islamic teachings. This research has succeeded in revealing the public's assessment of Salafi studies in Padang City. These five assessments can be used as a reference for writers in developing research as well as gathering information about Salafi studies.